Uf, quin dissabte, rateta Arbequina!: una reescriptura feminista del conte tradicional català La rateta que escombrava l’escaleta per Maria-Mercè Marçal - Sandrine Frayssinhes Ribes (Catalonia)
The work of Maria-Mercè Marçal (1952-1998) has become an essential reference in the history of Catalan poetry in the 20th century, especially for her feminist commitment and rebelliousness. In this article, my aim is to present one of her stories entitled Uf, quin dissabte, rateta Arbequina, written in 1988, which the author herself defined as an adaptation of the traditional Catalan tale La rateta que escombrava l'escaleta. While maintaining the structures of the Catalan folk tale, Marçal writes a new story of the famous character of the little rat, a modern narrative, the definition of which is somewhere between a wonderful tale and a testimony. Following the movement of tension between tradition and subversion that is constant in her work, the poetess subverts the traditional tale to make it a feminist testimony of the 20th century, faithful to her commitment.